Contact ultrasound strengthened far-infrared radiation drying on pear slices: Effects on drying characteristics, microstructure, and quality attributes. Issue 6 (26th April 2019) - Liu, Yunhong; Sun, Changying; Lei, Yuqing; Yu, Huichun; Xi, Huihan; Duan, Xu
Abstract: In order to investigate the feasibility and the enhancing effect of contact ultrasound application during far-infrared radiation (FIR) drying, a contact ultrasound strengthened FIR (CUFIR) drying equipment was fabricated and used, and CUFIR drying experiments on pear slices were carried out to explore the synergetic effects of ultrasound power and FIR heating on drying characteristics, microstructure, and quality of dried pear products. The results show that the application of contact ultrasound could be obviously helpful to accelerate internal mass transfer in pear slices and improve the drying rate of FIR drying, and higher ultrasound power could lead to stronger strengthening effect. The enforcing effect of ultrasound increased at higher FIR power, and weakened with the reduction of moisture content during CUFIR drying. The D eff values ranged from 4.76 × 10 −10 m 2 /s to 13.94 × 10 −10 m 2 /s in this study and the increase of both FIR power and ultrasound power had significant and positive influence on the increasing of D eff values. With scanning electrical microscope (SEM), it was observed that the improvement of ultrasound power could enlarge the size of microcapillaries and even generate new micropores and microchannels on the ultrasound-treated surface and in the organism structure of pear slices. The increase of ultrasound power could improve total phenolic content (TPC) and total flavonoids content (TFC) of pear slices at FIR powers of 100 and 220 W. Yet, the application of contact ultrasound with ultrasound power of 60 W had negative influence on TPC and TFC at FIR power of 340 W. Although the ascorbic acid content (AAC) reduced as FIR powers increased during FIR drying without contact ultrasound assistance, the increase of ultrasound power could improve AAC at all FIR powers. The CUFIR drying at ultrasound power of 60 W and FIR power of 220 W achieved the lowest energy consumption. Therefore, the application of FIR drying combined with contact ultrasound is a promising method to improve drying rate as well as protect product quality.